Cross-border accessibility and spatial development in Portugal and Spain - Anabela Ribeiro; Jorge Silva (European Regional Science Association (ERSA), 2010)
Cross-border regions' development is one of the EU major current concerns. These regions are usually less dynamic socio-economically and correspond to peripheral areas within each country. Some of these regions have recently benefited from the existence of new roads, which investment was mainly possible through the European financial programme of Transnational Transport Networks, TEN-T. Almost twenty years after its implementation start, and after initial observations on the impacts, some development problems get unexpectedly worst. Moreover, the accessibility role in regional development is not effectively accounted in the actual scientific production and the work devoted to this issue is not significant, even less if devoted to cross-border accessibility. An investigation is starting now in Portugal, using statistical spatial analysis (including spatial regression analysis and spill over analysis), to evaluate how accessibilities from each side of the border influence the other side, and how corresponding municipalities influence each other socio-economically. Using socioeconomic data from the all cross-border extension between Portugal and Spain a model will be calibrated, able to measure the relation between accessibility and development. In an early stage, it is important to look through the behaviour of both sides of the border separately, preparing the modeling process with accuracy. This initial study also prepares the setting for a more complete study including both sides of the border, therefore including Spanish data. This paper presents the spatial behaviour for a set of socioeconomic development variables including accessibility, in all the Portuguese municipalities in the border (including first and second neighbours) and for the periods of 1981-1991 and 1991-2001. This spatial behaviour analysis lead to two main conclusions: some tendencies were previously detected intuitively and this study just confirms it. Other interesting tendencies in the relationship between accessibility and development on the border region were only detected by using spatial analysis techniques. These latter tendencies represent important criteria to account for on the management and planning of existing and future transport infrastructures between the two countries.
Keywords: 330